2020
DOI: 10.2166/ws.2020.215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field and Mg2+ doping on calcium carbonate scaling shown in experiments and first principle calculations

Abstract: The effect of electric field applied and Mg2+ doped on formation of calcium carbonatescale in circulating cooling water is investigated by using home-made experimental device, which can simulate the scaleof formationin local power plant. The results showthat high-voltage electrostatic fields and magnesium ions can inhibit scale growthin circulating cooling water. When the magnesium ion concentration is 4 mmol/L, the scale inhibition effect is the best under the action of the electric field (6 kV), and its scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In addition, the XRD spectra of (Mg, Ca)CO 3 and CaCO 3 are identical, supporting the hypothesis that Mg 2þ may enters the calcite lattice. This is consistent with the conclusion of Gao et al (2020). Large amounts of calcite forming on the heat exchanger surface and in solution are beneficial to achieve scale inhibition.…”
Section: Sem and Xrd Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the XRD spectra of (Mg, Ca)CO 3 and CaCO 3 are identical, supporting the hypothesis that Mg 2þ may enters the calcite lattice. This is consistent with the conclusion of Gao et al (2020). Large amounts of calcite forming on the heat exchanger surface and in solution are beneficial to achieve scale inhibition.…”
Section: Sem and Xrd Analysissupporting
confidence: 91%
“…These results indicate that the hardness of the water affects the treatment effect of the high voltage electrostatic field. Previous studies have shown that the electrostatic field treatment of hard water with high levels of hard ions promotes scaling, while the electrostatic field treatment of artificial hard water with low levels of hard ions showed the effect of scale inhibition (Gao et al 2020).…”
Section: Scale Inhibition Ratementioning
confidence: 96%
See 3 more Smart Citations